ADMINISTRATION OF LACTULOSE IN COMPLEX PEHABILITATION TREATMENT AFTER RADICAL AND RECONSTRUCTIVE RESTORATIVE SURGERY OF BOWELS IN CHILDREN - I.V. Kirgizov; I.A. Shishkin; A.A. Gusev; P.V. Ivanov (Вопросы современной педиатрии, 2009)
The results of treatment of children (n = 64) of 1,5–17 years old, receiving rehabilitation course after reconstructive — restorative surgery of bowels are presented in this article. It was shown, that prolonged (1 month and more) administration of lactulose (Duphalac) results in improvement of motor and evacuation function of bowel, and decreases «sensor inability» of reduced parts of bowel. As a result, lactulose stimulates functioning of «obturative apparatus of neoampula» (voluntary evacuation, retention of intestinal contents), that favors to increase of quality of life and social rehabilitation of children in outlying post surgical period. Key words: children, post surgical rehabilitation, «idiopathic megacolon»syndrome, Hirschsprung's disease, anorectal malformations,lactulose. (Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(2):34-37)